The oral microbiota of patients with recurrent aphthous stomatitis - Bankvall, Maria; Sjöberg, Fei; Gale, Gita; Wold, Agnes; Jontell, Mats; Östman, Sofia (Journal of oral microbiology, 2014)
Specific pathogenic bacteria have been implicated in recurrent aphthous stomatitis (RAS), a chronic inflammatory condition characterised by ulcerations in the oral mucosa. However, the aetiology behind this condition still remains unclear. The buccal microbiota of patients with RAS was compared to that of control subjects to investigate its potential role for this condition. Buccal swabs were obtained from non-ulcerative areas of 60 patients, of whom 42 patients had lesions at the time of sampling, and 60 healthy age- and gender-matched controls. Bacterial DNA was extracted and analysed by Terminal-Restriction Fragment Length Polymorphism, using enzymatic digestion of the polymerase chain reaction-amplified 16S rRNA gene, yielding a series of peaks, each representing a bacterial taxon. Two peaks, 60 and 489, were more prevalent in patients with RAS than controls. Conversely, peaks 58 and 490 were less common in patients than controls. When the patients were divided into subgroups, we found that the observed differences in peak-pattern were related to the presence of lesions during sampling. The microbiota of the non-inflamed buccal mucosa differed between patients and controls. The differences were most pronounced in patients who presented with lesions during sampling, suggesting that a disturbance in the normal buccal microbiota triggers the presence of lesions or that presence of lesions alters the microbiota.